Effects of Different Types of Honey on Wound Healing in rats - Hussin, Khaled. M. A.; El-Mabrok, Asma. Saleh. W.; Eissa, Nawara. M. B.; Husain, Akaram; Wanes, Marwan Saleh (Al-Mukhtar Journal of Sciences, 2018)
One hundred and twenty healthy female Sprague-Dawley rats weighing between 300 to 350g were used in this study over a 20-day period. They were allocated randomly into 4 groups of 30 animals each. After the creation of 2cm x 2cm open wound, Group I was control treated with Gentamycin ointment. Groups II, III and IV were treated with Different Types of Honey. On application, the honey was well accepted by the animals without any adverse reaction. On clinical examination, Groups II, III and IV showed bright beefy red color granulation tissue with angiogenesis when compared to Groups I. On bacteriological examination, Staphylococcus aureus, Pseudomonas, Escherichia coli, Proteus and Klebsiella species were isolated from all the groups. Mean percentage of epithelialistion, wound contraction and total healing were significantly better in Group IV (P<0.05). Honey can be a better wound healing biomaterial in rats. It can be used as a less expensive skin substitute in order to stimulate and promote wound healing in animals.